THE INFLUENCE OF ORGANIZATIONAL SUPPORT, EMPOWERMENT AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR AGAINST EMPLOYEE PERFORMANCE - Rahmi Mutiadewi Dalimunthe (Business and Entrepreneurial Review, 2014)
The background of this research is hospitals nowadays both private hospitals and public hospitals in many countries inclusive Indonesia are constantly adapting to the challenges of both the external and internal environment. Therefore, the hospitals must pay attention to the market and relevant changes to rearrange the state of strategic management for improving job performance of their employees in order to enhance customers satisfaction.The main objective of this research was to explore the effects of perceived organizational support, empowerment, and organizational citizenship behavior on job performance.The Data for this study were collected using purposive sampling techniques to 250 u.s. nurses samples in private hospitals that operating in Jakarta. A total of 220 questionnaires were retrieved and out of which 13 were invalid. Therefore, 207 questionnaires were usable for analysis, representing the usable response rate of 82.8% SPSS for windows version 19 was self-employed for data analysis to explore descriptive statistics , and correlation analysis. For testing hypotheses was using multiple regression and hierarchical multiple regression by reviewing the regression coefficients and coefficients of determination with a level of significant of  0.5The results of this research that the effect of perceived organizational support was found positively and significantly influenced job performance; the effect of organizational citizenship behavior was found positively and significantly influenced the on-the-job performance. The conclusion of this research is that the three hypotheses that were being given can be accepted. The limitations of this study, production management, implication, and suggestions for future research are discussed in this thesis.